2014
DOI: 10.1123/ijspp.2013-0526
|View full text |Cite
|
Sign up to set email alerts
|

Motion Characteristics of Women’s College Soccer Matches: Female Athletes in Motion (FAiM) Study

Abstract: The current findings provide novel insight linking the developmental progression between youth and high-level matches for overall demands and work rates. Moderate- and high-intensity distances cumulatively range from 2100 to 2600 m (26-28% total distance) in female college matches. The high amount of consistency observed for the proportions of distance covered suggest that substitution patterns have little impact on locomotor distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
111
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(124 citation statements)
references
References 28 publications
10
111
2
1
Order By: Relevance
“…These positional differences in aerobic power are in agreement with corresponding differences during match play, where it has been noticed that midfielders cover larger distances than defenders [2]. In addition, research on young soccer players has shown that midfielders cover a greater distance than defenders, especially in low-and moderate-speed running, whereas attackers were recorded with higher values than midfielders in sprint distance, number of sprints, and maximum speed [5].…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…These positional differences in aerobic power are in agreement with corresponding differences during match play, where it has been noticed that midfielders cover larger distances than defenders [2]. In addition, research on young soccer players has shown that midfielders cover a greater distance than defenders, especially in low-and moderate-speed running, whereas attackers were recorded with higher values than midfielders in sprint distance, number of sprints, and maximum speed [5].…”
Section: Introductionsupporting
confidence: 70%
“…Typically, soccer players are classified into four groups: goalkeepers, defenders, midfielders, and attackers [1][2][3][4][5], although another classification system has been used, grouping players into goalkeepers, central defenders, full backs, central midfielders, wide midfielders, and attackers [6]. These studies have revealed differences in the physiological characteristics depending on player position.…”
Section: Introductionmentioning
confidence: 99%
“…The activity profiles of male and female soccer players during matches have been described by many authors (Andersson et Vescovi and Favero, 2014). Most of these studies showed that the distance a player covers on a full-sized pitch during a match is dependent on the playing position.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the professional male players, collegiate players spend less time walking and jogging during a soccer game, and more relative time running and sprinting ( Figure B-6). 196 There is a need for a laboratory-based exercise protocol that models the demands of amateur soccer including unanticipated changes of direction. Given the nature of the sport, it can be assumed that most of the 5,000 turning events during a soccer game 25 are in response to movement on the field and require some level of decision-making.…”
Section: Modeling Sportmentioning
confidence: 99%
“…College players spend less time walking compared to professional players. 30,196 Furthermore, all current time motion analyses in soccer only represent a single soccer match which may not best represent the demands an athlete experiences over the course of season (Table B-1).…”
mentioning
confidence: 99%